Kajian Sosial Ekonomi Nelayan Rajungan Pengguna Alat Tangkap Bubu di Kecamatan Soropia Kabupaten Konawe - Lestari, Indri; Yusuf, Sarini; Kamri, Syamsul (Jurnal Sosial Ekonomi Perikanan, 2021)
The coastal area of Konawe Regency is an area in Sountheast Sulawesi where the population mostly works as fisherman, one of which is in Soropia Subsdistrict, especially in Mekar and Leppe Villages, which are swimming crab-catch areas using traditional crab trap. This study aims to determine the social economic conditions of swimming crab fishermen in those villages. This research was conducted from February to March 2020. The respondents were all crab trap fishermen which consisted of 7 fishermen. Data were collected using questionnaire and direct observation to the fishermen houses. Primary data such as the area of the house, the type of house floor, the type of the house walls, the bathroom, the source of lighting, the source of drinking water, fuel consumption, clothing, income, health condition, education level family savings, family savings, age, work experience, fishing gear, and catch data were, collected directly from crab fishermen through interviews. Secondary data such as village area and population werw obtained from various sources or agencies such as Central Bureau of Statistics SE-Sulawesi and sub-district office, The data were then analyzed using descriptive qualitative analysis using social economic criterions guidelines from Central Bureau of Statistics The results of this stu dy showed that all crab trap fishermen were categorized as poor and marginalized Out of 14 criteria for the pooraccording to Central Bureau of Statistics, only 9 criteria that were fulfilled, Five criteria for the poor that were not fulfilled, such as the size of the house measuring of only 5 x 7 m and 6 x 8 m, source of household lighting was not electricity, only buy one new set of clothes in a year, health condition such as itching, fever and cough, the highest income was IDR 2.100,000-2.520.000, medium income was IDR 1.2600,000-1.470.000, and the lowest was IDR 650.000. Therefore, the development of crab fisheries must take into consideration the welfare of fishermen not only the sustainable of the resources